Aroma profile of gowe, a traditional malted fermeted Sorghum beverage from Benin - Vieira-Dalodé, Générose (My University, 2016)
Spontaneous fermented gowé was characterized by specific flavor produced by different enzymatic activities of microorganisms involved. Gowé was also produced by controlled fermentation using strains of Lactobacillus fermentum and Weissella confusa singly or in combination with Kluyveromyces marxianus and Pichia anomala after an accelerated saccharification. Investigation using Likens-Nikerson extraction method and gas chromatography-mass spectrometry (GC-MS) analysis revealed that the volatile compounds identified in the product obtained by spontaneous and controlled fermentation were composed of alcohols, aldehydes, acids, esters, hydrocarbons, furan, phenol and piperidine. The use of the starter cultures preceded by an accelerated saccharification led to a drastic reduction in the volatile components concentration for the inoculated samples. A principal component analysis performed revealed an important concentration of volatile acids in the inoculated samples.
Keywords: Sorghum; Fermentation; Starter culture; volatile coumpound